Photon-Working Switches - Yokoyama, Yasushi; Nakatani, Keitaro; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This book focuses on photoswitches. The objective of the book is to introduce researchers and graduate course students who are interested in "photon-working switches" not only to the fundamentals but also to the latest research being carried out in this field. Light can reach a target substrate without any physical contact to deliver energy. The energy can induce changes in the structure of the molecules included in the substrate so that its properties and functions are made switchable by light irradiation. When a substrate is able to revert to its original state, this system can be regarded as a "photon-working switch". The terms "photon-working switches" or "photoswitches" are almost equivalent in meaning to "photochromism"; however, they focus on the "switching of functions" of chemical species rather than their "reversible transformation". Most of the authors of this volume are members of PHENICS, an international research group on organic molecular photoswitches composed of research institutions from France, Japan, Russia, China and Germany. Since its inception in 2008, PHENICS has promoted active research to develop the field. This book commemorates the group's eighth year of collaborative research.
New trends in spiro-compounds photochromic metals sensors: quantitative aspects -- Novel ethene-bridge diarylethene photochromic systems: self-assembly, photo-switcher and molecular logic gates -- Properties and application of indolinooxazolidines as photo-, electro- and acidochromic units -- Strategies for switching with visible light -- Turn-on mode fluorescent diarylethenes -- Fluorescent switchable diarylethene derivatives and their application to the imaging of living cells -- Photochromism of Pentaarylbiimidazoles and Phenoxyl-Imidazolyl Radical Complexes -- Diarylethenes that Photoswitch with Visible Light -- Light-sensitive organic recording media for three-dimensional optical memory -- Photochromism of naphthopyrans possessing a Spirophenanthrene unit and the ophthalmic lens comprising of them -- Multiphoton-gated photochromic reactions induced by pulsed laser excitation -- Ultrafast Photoswitching Dynamics of Azobenzenes with Intra- and Intermolecular Constraints -- Polyfunctional photochromic magnetic materials based on 3d metal (tris)oxalates -- Photo-Modulation of Superconducting and Magnetic Property -- NMR spectroscopy to investigate switching reactions -- Modeling Diarylethenes Excited States with Ab initio Tools: from Model Systems to Large Multimers -- Photochromic crown ethers -- Linear and Nonlinear Optical Molecular Switches Based on Photochromic Metal Complexes -- Supramolecular photochromism of bis(phenanthrolinylthienyl)hexafluorocyclopentene -- Cooperative Self-Assembly of Photochromic Diarylethenes at Liquid/Solid Interface and Highly Sensitive Photoinduced Transformation of the Ordering -- New strategies for light-induced alignment and switching in liquid crystalline polymers -- Photoswitchable hybrid nanosystems based on diarylethene molecules and gold nanoparticles.
Keywords: Physical chemistry; Optical materials; Polymers; Physical Chemistry; Optical Materials; Polymers